Development of Technology-Based Learning Media Using Tiktok Filters on the Material of the Proclamation of Indonesian Independence on the Learning Outcomes of Class XI Students of SMA N 12 Semarang - R. Soeharso; Zerlinda Nova Ardelia (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The purpose of this research is to develop technology-based learning media using TikTok filters in the context of history education. With the advancement of technology and social media, TikTok has become one of the most popular platforms among learners. Therefore, by using the interactive features it contains, learners can improve engagement and learning outcomes in learning. This study involves the design and implementation of TikTok filters tailored to relevant historical materials, such as important events and historical figures. This research uses the RnD method. TikTok filters will be created and tested with groups of students to assess their effectiveness in improving understanding and learning outcomes. Test results show that the use of TikTok filters in the history classroom creates a more engaging and enjoyable learning experience and improves learners' understanding of the historical material taught. It is hoped that this approach will make history learning more accessible to the digital generation who are accustomed to social media, while utilizing technology to support a more effective and interactive learning process.